Pengaruh Strategi Inovasi dan Lingkungan Kerja Terhadap Kinerja UMKM (Survei Pada UMKM Mie Bakso di Kota Sukabumi) - Alfyan Ramadhani; Erry Sunarya; Sopyan Saori (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The challenge encountered by SMEs in Indonesia concerning innovation and performance stems from a flaw in their innovation development approach, resulting in the underperformance of Indonesian SMEs compared to their counterparts in different nations. Currently, the advancement of innovation is recognized as a crucial strategy in enhancing the quality of MSMEs, enabling them to maintain competitiveness, particularly within the food industry. The research was aimed at determining the amount of the influence of Innovation Strategy and Work Environment towards the Performance of Mie Bakso MSMEs in Sukabumi city. The research methods applied were descriptive and associative with quantitative approach. The technique of sampling deployed was purposive sampling by distributing questionnaires to 42 respondents in line with the required criteria. The technique of analyzing data used in the research was multiple linear regression. The results of the research, based on the determination coefficient calculation, reveal that 42.3% of the influence on MSMEs performance can be attributed to the innovation strategy and work environment, while the remaining 57.7% is influenced by other variables not examined in the research. The simultaneous test (F-test) and partial test (T-test) show that both innovation strategy and work environment have a significant influence towards MSMEs performance.